Murder on the Kansas City Special?: Pullman porters, emotions, and the strange case of J. H. Wilkins - Pearce, Rosemary (Cambridge University Press, 2019)
J. H. Wilkins, an African American railroad porter for the Pullman Company, was killed while on duty in April 1930. How he met his death has never been fully determined, but the Pullman Company’s investigation file exposes the dangerous and racialised emotional terrain that porters navigated daily on their journeys across the US. By examining Wilkins’ death, and the work of Pullman porters more broadly, this article makes the case that white control of black emotions in occupational and public spaces was a significant characteristic of the Jim Crow era, and demands further scholarly attention.